2022
DOI: 10.1038/s12276-022-00889-8
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial citrate accumulation drives alveolar epithelial cell necroptosis in lipopolysaccharide-induced acute lung injury

Abstract: Necroptosis is the major cause of death in alveolar epithelial cells (AECs) during acute lung injury (ALI). Here, we report a previously unrecognized mechanism for necroptosis. We found an accumulation of mitochondrial citrate (citratemt) in lipopolysaccharide (LPS)-treated AECs because of the downregulation of Idh3α and citrate carrier (CIC, also known as Slc25a1). shRNA- or inhibitor–mediated inhibition of Idh3α and Slc25a1 induced citratemt accumulation and necroptosis in vitro. Mice with AEC-specific Idh3α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 56 publications
0
32
0
Order By: Relevance
“…To sum up, RIPK1-RIPK3-MLKL signaling cascade triggers necroptosis. 8,15,25 In 2004, necroptosis has been implicated in bronchoalveolar fluid (BALF) of ALI patients. 26 In high-dosed lipopolysaccharide (LPS)-induced ARDS animal models, increased phosphorylated RIPK3 and MLKL were demonstrated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To sum up, RIPK1-RIPK3-MLKL signaling cascade triggers necroptosis. 8,15,25 In 2004, necroptosis has been implicated in bronchoalveolar fluid (BALF) of ALI patients. 26 In high-dosed lipopolysaccharide (LPS)-induced ARDS animal models, increased phosphorylated RIPK3 and MLKL were demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that necroptosis, a new form of regulated cell deaths (RCDs), plays a role in the pathogenesis of ALI/ARDS. ,, Necroptosis, first defined by Yuan group, can be activated in a wide range of human inflammatory-involved diseases. Mechanism of necroptosis has been relatively clear by numerous efforts in the past 2 decades . Various death receptors, such as TNF receptor-1 (TNFR1), CD95 (Fas), interferons (IFNs), and IFN-induced Z-DNA binding protein 1 (ZBP1), could initiate necroptosis pathway. Briefly exemplified by TNFR1, tumor necrosis factor-α (TNF-α) interacts with TNFR1 to form signaling complex I on the membrane .…”
Section: Introductionmentioning
confidence: 99%
“…Necroptosis results in the disrupture of the cellular membrane and the release of components, including DAMPs and inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), which can cause a self-amplified inflammatory process [ 13 ]. Our recent studies found that L‐OPA1 deficiency and mitochondrial citrate accumulation mediate mitochondrial fission, induce necroptosis of alveolar epithelial cells, and exacerbate ALI [ 10 , 14 ]. For macrophages, the human respiratory syncytial virus (RSV) induces necroptosis of macrophages, aggravating pneumonia [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Necroptosis leads to the rupture of the cell membrane and the release of various intracellular components, including DAMPs and inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), to self-amplify or even trigger the inflammatory process [12]. Our recent studies found that L-OPA1 deficiency and mitochondrial citrate accumulation mediate mitochondrial fission, induce necroptosis of alveolar epithelial cells, and exacerbate ALI [9,13]. For macrophages, the human respiratory syncytial virus (RSV) induces necroptosis of macrophages, aggravating pneumonia [14].…”
Section: Introductionmentioning
confidence: 99%
“…Excessive mitophagy is maladaptive and associated with cell death [30]. Recently, we have reported that excessive mitochondrial fission induced by mitochondrial citrate accumulation contributes to necroptosis by triggering mitophagy in alveolar epithelial cells [13]. Thus, mitochondrial fission would be a key mechanism triggering necroptosis.…”
Section: Introductionmentioning
confidence: 99%